2010
DOI: 10.1016/j.aap.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Safety climate and the Theory of Planned Behavior: Towards the prediction of unsafe behavior

Abstract: [Abstract] The present study is concerned with the human factors that contribute to violations in aviation maintenance. Much of our previous research in this area has been based on safety climate surveys and the analysis of relations among core dimensions of climate. In this study, we tap into mainstream psychological theory to help clarify the mechanisms underlying the links between climate and behavior. Specifically, we demonstrate the usefulness of Ajzen's (1991Ajzen's ( , 2001) Theory of Planned Behavior (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
177
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(198 citation statements)
references
References 21 publications
(33 reference statements)
13
177
0
1
Order By: Relevance
“…Christian and colleagues (2009) found that safety performance was positively related to both locus of control and safety attitudes and negatively related to propensity for risk taking, although none of these relationships were strong. Another study found that individuals who do not value the importance of safety behaviors, feel pressured not to engage in safe behaviors, or do not feel like they have control over their own safe behaviors are not likely to engage in safe behaviors (Fogarty & Shaw, 2010). The above findings suggest that in addition to lack of knowledge and motivation, individual characteristics of trench workers could provide some explanation for why workers are not engaging in proper trenching-safety behaviors.…”
Section: Individual Antecedents Of Safety Performancementioning
confidence: 96%
“…Christian and colleagues (2009) found that safety performance was positively related to both locus of control and safety attitudes and negatively related to propensity for risk taking, although none of these relationships were strong. Another study found that individuals who do not value the importance of safety behaviors, feel pressured not to engage in safe behaviors, or do not feel like they have control over their own safe behaviors are not likely to engage in safe behaviors (Fogarty & Shaw, 2010). The above findings suggest that in addition to lack of knowledge and motivation, individual characteristics of trench workers could provide some explanation for why workers are not engaging in proper trenching-safety behaviors.…”
Section: Individual Antecedents Of Safety Performancementioning
confidence: 96%
“…e TPB considers individual and environmental influence and could be used to explain human behaviour in a satisfactory extend. A search of existing literature showed that TPB has been cited more than 10,000 times and successfully applied in various research fields to predict safety-related behaviour such as unsafe driving behaviour [18], green exercise [19], and the relationship between safety climate and unsafe behaviour [10,11].…”
Section: Tpb and Construction Safety Researchmentioning
confidence: 99%
“…Individually, "not willing to perform safely" can be considered as a decision-making process [8] and can be explained with psychological theories because they address how the mind, perceptions, and beliefs influence safety behaviour. e prevailing theoretical framework of unsafe acts is the eory of Planned Behaviour (TPB) [9], and it has been widely applied to analyse unsafe acts in construction [10,11] and other research fields.…”
Section: Introductionmentioning
confidence: 99%
“…The theory explains the psychological aspects of employee behavior and the principal assumption of the TPB has to do with the intentions behind any human action. Per Fogarty and Shaw (2009), an individual's own attitude toward behavior, subjective norms, and perceived behavioral control can be used to predict intentions regarding any safety issue. Intention can in this way be used to predict actual safety behavior.…”
Section: Literature Reviewmentioning
confidence: 99%